INDEKS TREYNOR, SHARPE DAN JENSEN TERHADAP KEBIJAKAN DEVIDEN DI BURSA EFEK INDONESIA - Sari, Pristin Prima; Hermuningsih, Sri; Hidayat, Riskin; Rinofah, Risal; Setiawan, Eko Agus (Jambura Economic Education Journal, 2026)
Investors need to understand the performance of the Treynor, Sharpe, and Jensen indexes to assess the performance of their stock portfolios. The objective of this study is to empirically examine the effect of the Treynor, Sharpe, and Jensen indexes on dividend policy in December and January 2021-2025. The research method used is quantitative multiple regression analysis using IBM SPSS 22 statistical tools. The benefit of this study is to develop portfolio management research. Results show that there is a significant difference between the Sharpe, Treynor, Jensen Index and the December Dividend. there is a significant difference between the Sharpe, Treynor, Jensen Index and the January Dividend. The results for January and December indicate that the stock performance indices—Treynor, Jensen, and Sharpe—have a significant influence on dividend policy. The higher the value of each index, the greater the company's tendency to increase dividend policy. This indicates that companies tend to use risk-adjusted performance as a basis for dividend distribution decisions.